2021
DOI: 10.3390/molecules26164849
|View full text |Cite
|
Sign up to set email alerts
|

Orexins/Hypocretins and Cancer: A Neuropeptide as Emerging Target

Abstract: Over 20 years ago, orexin neuropeptides (Orexin-A/hypocretin-1 and Orexin-B/hypocretins-2) produced from the same precursor in hypothalamus were identified. These two neurotransmitters and their receptors (OX1R and OX1R), present in the central and peripheral nervous system, play a major role in wakefulness but also in drug addiction, food consumption, homeostasis, hormone secretion, reproductive function, lipolysis and blood pressure regulation. With respect to these biological functions, orexins were involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 71 publications
0
25
0
Order By: Relevance
“…Among this large family, we have demonstrated in 2011 that OX1R, but not OX2R, was ectopically expressed in colon cancer whatever its location and/or grade of development ( 15 ). The OX1R activation in colon cancer cells by exogenous orexins (OxA or OxB) induced the mitochondrial caspase-dependent apoptosis ( 28 ) The OxA/OX1R system was responsible for the anti-tumoral impact in preclinical models in which colon cancer cells were xenografted and also in preclinical models where pancreatic or liver cancer cells were xenografted ( 15 , 19 , 29 ). Usually, the first or second line of pancreatic cancer treatment, notably in metastatic pancreatic cancer, involved gemcitabine and Nab-paclitaxel ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among this large family, we have demonstrated in 2011 that OX1R, but not OX2R, was ectopically expressed in colon cancer whatever its location and/or grade of development ( 15 ). The OX1R activation in colon cancer cells by exogenous orexins (OxA or OxB) induced the mitochondrial caspase-dependent apoptosis ( 28 ) The OxA/OX1R system was responsible for the anti-tumoral impact in preclinical models in which colon cancer cells were xenografted and also in preclinical models where pancreatic or liver cancer cells were xenografted ( 15 , 19 , 29 ). Usually, the first or second line of pancreatic cancer treatment, notably in metastatic pancreatic cancer, involved gemcitabine and Nab-paclitaxel ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, TRT has expanded to treat a wider range of targets and tumors in addition to thyroid, with a steadily increasing number of radiopharmaceuticals in preclinical and clinical development [ 19 , 20 , 73 , 74 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. Consequently, TRT represents an unprecedented opportunity for personalizing medical radiation by sex and hormonal status before rather than after the patients who are the most vulnerable (namely, young females) and can benefit most from individualized, well-informed therapy, become statistics in the large and long follow-up studies necessary to establish secondary cancer risks from medicinal irradiation.…”
Section: Sex Hormonal Status and Targeted Radionuclide Therapy: A Cha...mentioning
confidence: 99%
“…Therefore, both endogenous orexins and OX1R have no impact on tumor growth, and they can only affect malignancy in the presence of exogenous orexins. [ 207 ] Despite the lack of orexins within tumors, OxA expression can be detected in “fiber‐like” stroma surrounding prostate tumors and follicular exocrine epithelia, [ 208 ] indicating a possible impact on tumor growth through stromal cells within the TME. Therefore, the orexin/OXR system probably acts through paracrine effects on cancerous cells.…”
Section: Neuropeptides and Their Receptors In Cancermentioning
confidence: 99%
“…Generally, the cAMP pathway activates relevant enzymes and regulates gene expression, JNK, ERK1/2, and PI3K/Akt activation triggers cell proliferation, cell cycle progression, and apoptosis suppression, while p38/MAPK participates in programmed cell death. [207,209] More recently, Voisin et al revealed that the orexin/OX1R system induced a mitochondrial apoptosis response, which is driven by a new signaling pathway including immunoreceptor tyrosine-based motifs (ITIM) and the tyrosine-protein phosphatase nonreceptor type (SHP2) both in Chinese hamster ovary (CHO) cells and colon cancer cells. [210] In conclusion, recent studies on orexin signaling provides a wide range of possibilities in the treatment of certain cancers; however, we are still at an early stage in this novel field and much future work is required.…”
Section: Orexins/hypocretinsmentioning
confidence: 99%